AFFIXES IN SONG LYRICS OF ADELE - Unpris Yastanti; Widya Warlina (Center of Language and Cultural Studies [CLCS], 2018)
The purpose of this study is to identify Affixes on songs lyric of Adele in her latest albums “25”. Descriptive qualitative is used as the method of the analysis. The research data in this analysis was taken from Song Lyrics of Adele in her latest albums “25”. The result of this research are; (1). There are 22 words Suffixes and two words Prefix (2). There are seven adjective, nine plural, five nouns, two verbs, and one preposition.